Operational Analysis in Improving the Performance of Educational Institutions with the Total Quality Management (TQM) Model: at The Al-Ghuraba Foundation, Dompu Regency, West Nusa Tenggara - Awlya Hamlatul Arsy; Slamet Riyadi; Fausta Ari Brata (Jurnal Manajemen Bisnis, 2026)
This study analyzes the operational management functions, challenges, and TQM implementation at the Al-Ghuraba Foundation in Dompu to formulate strategies for performance improvement. Utilizing a qualitative case study approach, data were gathered through interviews, observations, and documentation. The findings indicate that operational management has evolved into strategic management through SWOT and SMART analyses, despite facing hurdles such as manual administrative systems. Key challenges include financial vulnerability due to a heavy reliance on School Operational Assistance (BOS) funds, high teacher turnover, and administrative burnout. The implementation of TQM highlights a Service Quality Paradox, where the institution's moral assurance compensates for its physical limitations. Consequently, this study proposes an Integrated TQM and Entrepreneurial Management model to synergize educational quality with financial independence.